Postrenal Failure due to Urinary Stones Associated with Acute Viral Gastroenteritis: Three Case Reports - Satoru Kira; Takahiko Mitsui; Hidenori Zakoji; Tadashi Aoki; Norifumi Sawada; Tatsuya Miyamoto; Masayuki Takeda (Case Reports in Urology)
Acute gastroenteritis with viral infection in infants causes severe diarrhea and often results in acute renal failure due to severe dehydration. However, a viral infection, particularly rotavirus, rarely induces postrenal failure due to bilateral stones in infants. Herein, we report three cases of postrenal failure in infants due to bilateral ureteral stones induced by acute gastroenteritis with rotavirus. Following immediately nephrostomy, chemical dissolution therapy succeeded to treat postrenal failure. Immediate nephrostomy for the release of upper urinary tract obstruction combined with urinary alkalization as a chemical dissolution therapy should be considered in such cases.